Parasocial Interaction as a Mediator: Unraveling the Influence of Social Media Influencers on Purchase Intentions - Heru Tri Sutiono; Aruna Kintamani Hayumurti; Tugiyo Tugiyo; Sri Harjanti (Asia Pacific Journal of Management and Education (APJME), 2024)
This research aims to analyze the influence of social media influencers on the purchase intention of online shopping application users in Indonesia, by including parasocial interactions as a mediator. There were 200 respondents obtained through purposive sampling technique. Using PLS-SEM (Partial Least Squares Structural Equation Modeling), the research results reveal that (1) social media influencers have a positive and significant direct influence on purchase intention; and (2) the influence of influencers is not only direct but also through mediated parasocial interactions. These findings become valuable insights for marketers in increasing the effectiveness of marketing strategies through collaboration with influencers. Overall, this research underscores the critical role of social media influencers in shaping purchase intention among online shopping application users in Indonesia, emphasizing the significance of emotional connections and engagement in influencing consumer behavior. In summary, the study results underscore the notable impact of social media influencers on the intention to purchase among users of online shopping platforms in Indonesia.